Nereites in Lower Cretaceous marginal-marine facies from Patagonia: Ichnotaxonomic and ethological implications. (January 2018) - Fernández, Diana Elizabeth; Comerio, Marcos; Pazos, Pablo José
Abstract: Detailed descriptions of Nereites are uncommon. In this work, Nereites are thoroughly described from tidally influenced and wave dominated deposits in the Cretaceous of the Neuquén Basin (northern Patagonia). These Nereites show a great morphological variety in bedding-plane view. The application of different possible tracemakers for this renowned ichnogenus is discussed. Besides the well known morphology consisting of median tunnel surrounded by a halo composed of reworked material, a tripartite burrow structure has been observed that comprises in addition a disturbed, but not reworked zone at the external side of the reworking halo. The studied material provides evidence that the producers of these Nereites were shallow infaunal deposit-feeding organisms, a feeding strategy mentioned in many studies of the ichnogenus as matching a worm-like tracemaker, while the subsurface characteristics, particularly the disturbed outer zone, support a burrowing arthropod as tracemaker. Consequently, for interpretation of the potential trace producer, basic feeding strategy and burrow construction method should be differentiated and neither should be automatically linked with one particular tracemaker. The different morphologies of these Nereites allow referral of part of this material to N . missouriensis, but some cases of transitional forms remain problematic. The ratio between the width of the median tunnel and the enveloping zone (used as an ichnotaxobase) is not always due to variation in the burrowing depth of the producer. The same individual was able to produce wider or narrower enveloping areas in the same level along its course. In such cases, the use of this ichnotaxobase even at the ichnospecific level seems questionable. Graphical abstract: Highlights: First record of Nereites from the Cretaceous of northern Patagonia. Nereites exhibiting great morphological variety in shallow marine setting. Some Nereites exhibit a tripartite burrow fill (core, reworked zone, disturbed zone). Morphological features imply both worm-like and burrowing arthropod producer. Nereites ichnotaxobase needs refinement.